2015
DOI: 10.1016/j.bbmt.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Patients with Acute Myeloid Leukemia Relapsing after Allogeneic Hematopoietic Cell Transplantation: A Center for International Blood and Marrow Transplant Research Study

Abstract: Acute myeloid leukemia (AML) relapse after allogeneic hematopoietic cell transplantation (alloHCT) remains a major therapeutic challenge. We studied outcomes of 1788 AML patients relapsing after alloHCT (1990–2010) during first or second complete remission (CR) to identify factors associated with longer post-relapse survival. Median time of post HCT relapse was 7 months (mo; range, 1–177). At relapse, 1231 patients (69%) received intensive therapy, including chemotherapy (CT) alone (n=660), donor lymphocyte in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
231
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(252 citation statements)
references
References 23 publications
16
231
3
2
Order By: Relevance
“…233 Outcome for patients relapsing after allogeneic HCT during first or second CR is particularly poor. 234,235 The Center for International Blood and Marrow Transplant Research (CIBMTR) recently found 234 3-year OS was 4%, 12%, 26%, and 38% for relapses within 1 to 6 months, 6 months to 2 years, 2 to 3 years, and $3 years after allogeneic HCT, respectively. Lower mortality was independently associated with longer time from HCT to relapse and a first HCT using RIC; and inferior outcome associated with age .40 years, active GVHD, adverse cytogenetics, mismatched unrelated donor, and use of cord blood for first HCT.…”
Section: Salvage Treatmentmentioning
confidence: 99%
“…233 Outcome for patients relapsing after allogeneic HCT during first or second CR is particularly poor. 234,235 The Center for International Blood and Marrow Transplant Research (CIBMTR) recently found 234 3-year OS was 4%, 12%, 26%, and 38% for relapses within 1 to 6 months, 6 months to 2 years, 2 to 3 years, and $3 years after allogeneic HCT, respectively. Lower mortality was independently associated with longer time from HCT to relapse and a first HCT using RIC; and inferior outcome associated with age .40 years, active GVHD, adverse cytogenetics, mismatched unrelated donor, and use of cord blood for first HCT.…”
Section: Salvage Treatmentmentioning
confidence: 99%
“…Although small numbers meant the poor and very poor groups had to be combined for analysis, we demonstrate a significant adverse effect of adverse cytoge-netics on relapse and RFS, underlying the importance of considering the pretransplantation karyotype on prognosis. The relapse incidence of 61% at 3 years in these patients, along with currently re ported poor outcomes in those who relapse after transplantation [15,16], indicates the urgent need for strategies directed at prevention of post-HSCT relapse.…”
Section: Multivariate Analysismentioning
confidence: 99%
“…In a recent CIBMTR (Center for International Blood and Marrow Transplantation Research) analysis, patients with relapsed acute myelogeneous leukemia after mismatchedunrelated or double cord transplantation had a worse PRS than recipients of a matched sibling or matched-unrelated HCT. 8 The available treatment options for relapsed patients include intensive chemotherapy, donor lymphocyte infusion (DLI), withdrawal of immunosuppression, second allogeneic HCT and supportive care. [9][10][11] Theoretical concerns regarding severe uncontrolled GVHD resulting from the use of unmanipulated DLI in HIDT patients may lead to a reluctance to use DLI following relapse of malignancy in HIDT than following conventional matched donor transplants.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent CIBMTR (Center for International Blood and Marrow Transplantation Research) analysis, patients with relapsed acute myelogeneous leukemia after mismatchedunrelated or double cord transplantation had a worse PRS than recipients of a matched sibling or matched-unrelated HCT. 8 The available treatment options for relapsed patients include intensive chemotherapy, donor lymphocyte infusion (DLI), withdrawal of immunosuppression, second allogeneic HCT and supportive …”
mentioning
confidence: 99%